EN-40 : enhancing photocatalytic activity of Bi2WO6 under visible light irradiation through silver nanoparticles deposition - Xu, Wei Shen (2014)
Currently, photocatalyst has yet to be widely commercialised in wastewater treatment as existing photocatalysts like Titanium Dioxide (TiO2) still faces major drawbacks. Firstly, TiO2 is driven by ultraviolet (UV) light which is costly. Secondly, TiO2 has rapid charge recombination which leads to slow photodegradation. Bismuth Tungstate (Bi2WO6) is identified as an alternative to Titanium Dioxide (TiO2) since Bi2WO6 is visible light driven unlike TiO2. Due to Bi2WO6 weak visible light absorption, its photocatalytic activity remains low. Hence, there is a need to further increase its photocatalytic activity through means of material processing and modification. This establishes the goal of the report to improve Bi2WO6 photocatalytic activity through noble metal deposition. In this report, flower-like Bi2WO6 samples of average diameter 1.0µm to 2.5µm were synthesised by solvothermal process, using 260mg of Bismuth (III) Nitrate Pentahydrate (Bi(NO3)3.5H2O) with 160mg of Tungsten Hexachloride (WCl6) as precursors. Precursors’ concentration was increased by 50% and 100% and it was found that the concentration variation did not have obvious changes to the surface area and structure of Bi2WO6. The sample with concentration increased by 100% (BW-2) was chosen for noble metal deposition. Silver (Ag) loaded Bi2WO6, BW-A1 and BW-A2 were synthesised by the addition of Silver Nitrate (AgNO3) followed by photoreduction of 1h and 2h respectively, in visible light condition. BW-2, BW-A1 and BW-A2 were then characterised using XRD, FESEM, HRTEM, EDX and UV-Vis-DRS. XRD result exhibited diffraction peak at 38.1° which correspond to the plane (111) of Ag. In addition, SEM results clearly showed Ag nanoparticles with average size of 20nm deposited onto the Bi2WO6 surface. The UV-Vis-DRS absorption spectra of BW-A1and BW-A2 show much higher visible light absorption in the wavelength region between 400-900nm thus implying improved visible light absorption upon Ag nanoparticles deposition. Importantly, the photocatalytic activity of BW-2, BW-A1 and BW-A2 were assessed by the visible light photodegradation of Rhodamine B (RhB) and Methylene Blue (MB) dye. After 90min, BW-2 degraded 26.4% of RhB dye and 17.9% of MB dye; BW-A1 degraded 46.9% of RhB dye and 38.7% of MB dye; BW-A2 degraded 33.5% of RhB dye and 42.7% of MB dye. Generally, Ag loaded Bi2WO6 performed better than pure Bi2WO6 as shown by BW-A1 and BW-A2 reaction rate constant of 0.00751min-1 and 0.00490min-1 in RhB dye photodegradation. Both values are higher than BW-2 reaction rate constant of 0.00349min-1. This confirms the Ag nanoparticles deposition helps enhance photocatalytic activity. BW-A1 performed best among the samples as it is consistent in demonstrating good photodegradation efficiency for both RhB and MB dyes. This implies that a photoreduction time of 1h yields better photocatalytic activity than 2h. The reusability of BW-A1 was confirmed by the consistent photodegradation efficiency results obtained over six cycles of dye degradation performed under the same conditions.